Precious Crystal Gift Center / Yusnizar Mohamed Yusof... [et al.] - Mohamed Yusof, Yusnizar; Md Jaaafar, Halimatos Saadiah; Jusin, Hafsah; Md Yusoff, Siti Rohana; Abdul Rahman, Maya Azura (2001)
The Precious Gift Center is the store selling a various designs and shape of crystal for all occasion. They had purposely chosen a location that is situated in the building of Bukit Jambul Complex.They started their business on 1 January 2003